Financial and Marketing Determinants of Banking Performance in Indonesia: A Systematic Literature Review - Ade Ghofir; Viniyati Maftuchach (Jurnal Multidisiplin Sahombu, 2026)
This study conducts a systematic literature review to synthesize the financial and marketing determinants of banking performance in Indonesia. Drawing on Scopus-indexed empirical studies, the review integrates evidence on how traditional financial fundamentals, such as capital adequacy, asset quality, liquidity, and operational efficiency and marketing-based constructs, including service quality, customer satisfaction, loyalty, trust, and digital banking adoption, shape bank performance outcomes. The findings indicate that financial determinants remain the dominant predictors of profitability and stability, reflecting the prudential orientation of Indonesia’s banking regulatory environment. At the same time, marketing determinants increasingly function as strategic complements by enhancing customer retention and revenue stability in a competitive and digitally mediated market. However, the literature remains fragmented, with limited integrative models explicitly linking financial robustness to customer-based value creation. This review contributes by mapping dominant determinant clusters, identifying methodological and conceptual gaps, and proposing directions for integrative future research. The findings offer practical implications for bank managers and policymakers in designing performance strategies that are simultaneously financially robust and market-responsive to support sustainable competitiveness in Indonesia’s banking sector.